Perancangan Media Pembelajaran Berbasis Flash FlipBook Maker Pada Matakuliah Sistem Multimedia - Supriyadi Sandi (Jurnal Komunikasi, 2020)
The media is a tool that intersects in the process of teaching and learning for the achievement of educational goals in general and learning objectives in schools in particular. The media is also a means of transporting messages or information that is instructional or contain teaching purposes and is therefore called learning media. Many benefits can be taken from media management from what we know so far. The practical benefits of instructional media in the teaching and learning process are learning media that can clarify the presentation of messages and information so as to facilitate and improve the process and learning outcomes. The use of Flash Flipbook media can increase student learning motivation and can also affect student achievement or learning outcomes. It is expected that the results of this virtual module will have an impact on increasing students' mastery in learning the basics of multimedia systems.